An experimental investigation of frictionless flow in channels - Soh, Zhen Wei (2017)
Fluid flow is a fundamental aspect in many modern engineering applications. However, frictional loss has always been a cause of concern. Researchers have found that due to their favourable surface microstructures, surfaces with superhydrophobic property generate less friction when fluid flow pass. Among various methods of fabricating superhydrophobic surfaces, chemical immersion is one of the cheapest and most efficient method. The method constitutes 2 main steps: the etching of a surface followed by the lowering of its surface energy level.